Numerical simulation of overtopping in the earth-filled dam based on material point method. (September 2019) - Yang, Yong-Sen; Qiu, Liu-Chao; Tian, Lei; Li, Jing-Jun; Han, Yu
Abstract: Dams breach by overtopping is a serious natural disaster. Numerical simulation, as a efficient research method, is widely used to study the failure mechanism and predict the destroyed process of earth dams. Traditional numerical methods such as the finite element method (FEM) only provide the capacity of small deformation analyses due to mesh distortion. The Material Point Method (MPM), a mesh-free method, has been worked well for large deformation analyses. In this paper, a double-point MPM is introduced to analysis the failure process of earth-filled dams due to overtopping. Finally, it shows that the MPM predicts the flow propagation, the development of breach cross section and breach longitudinal profile well. Moreover, MPM provides an alternative method for the risk assessment of dam breach.